Involvement of small heat shock proteins (sHsps) in developmental stages of fall armyworm, Spodoptera frugiperda and its expression pattern under abiotic stress condition - Samanta, Snigdha (Heliyon, 2021)
Fall armyworm (FAW), Spodoptera frugiperda a recent invasive pest in India is reported to cause significant damage by feeding voraciously on maize and other economic crops from tropical to temperate provinces. It is becoming an arduous challenge to control the pest as it can survive in a wide range of temperature conditions and is already said to develop resistance towards certain insecticides. The small Heat shock proteins (hereafter, sHsps) are known to play an important role in adaptation of insects under such stress conditions. Our present study involved characterization of the three sHsps genes (sHsp19.74, sHsp20.7 and sHsp19.07) which encoded proteins of about 175, 176 and 165 amino acids with a conserved α-crystalline domain. Phylogenetic analysis of deduced amino acid sequences of the three genes showed strong similarity with the other lepidopteran sHsps. The effect of different growth stages on the expression profile of these stress proteins has also been studied and the Quantitative real time PCR (qRT-PCR) analysis revealed that the transcript level of sHsp19.07 and sHsp20.7 were significantly upregulated under extreme heat (44 °C) and cold (5 °C) stress. However, sHsp19.74 responded only to heat treatment but not to the cold treatment. In addition, the expression profile of all three sHsps was significantly lower in the larval stage (5(th) instar). Chlorantraniliprole treatment resulted in maximum expression of sHsp19.07 and sHsp20.7 after 12hr of exposure to the insecticide. Meanwhile, the same expression was observed after 8hr of exposure in case of sHsp19.74. These results proved that the sHsp genes of S. frugiperda were induced and modulated in response to abiotic stress, thus influencing the physiological function leading to survival of FAW in diversified climate in India.